2006
DOI: 10.1115/1.2728907
|View full text |Cite
|
Sign up to set email alerts
|

A Generalized Diffusion Layer Model for Condensation of Vapor With Noncondensable Gases

Abstract: The diffusion layer model for condensation heat transfer of vapor with noncondensable gases was originally derived on a molar basis and developed from an approximate formulation of mass diffusion, by neglecting the effect of variable vapor–gas mixture molecular weights across the diffusion layer on mass diffusion. This is valid for gases having a molecular weight close to that of the vapor or for low vapor mass transfer rates, but it may cause serious error if a large gradient in the gas concentration exists a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 16 publications
2
22
0
1
Order By: Relevance
“…9. This is of practical importance to the heat and mass transfer analogy approach in engineering calculations, where a convection-regime dependent correlation must be decided [27]. In contrast to Fig.…”
Section: Transition To Mixed Convection Regimementioning
confidence: 97%
“…9. This is of practical importance to the heat and mass transfer analogy approach in engineering calculations, where a convection-regime dependent correlation must be decided [27]. In contrast to Fig.…”
Section: Transition To Mixed Convection Regimementioning
confidence: 97%
“…Liao and Vierow et al [137,138] and Hogan et al [139] then expanded the diffusion layer model to the generalized diffusion layer model. They proposed that, from the kinetic theory of gases, Fick's law of diffusion was more appropriately expressed on a mass basis than on a molar basis; they also 9.…”
Section: Diffusion Layer Modelmentioning
confidence: 98%
“…Authors presented three different correlations, implementing the degradation factor method, diffusion layer theory, and the mass transfer conductance model. Liao and Vierow [13] indicated that the original diffusion model is valid for gases having a molecular weight close to that of the vapor or low vapor mass transfer rates, but serious error may arise if a large gradient in the gas concentration exists across the diffusion layer. The authors presented a generalized model which included the effect of variable mixture molecular weights across the diffusion layer on mass diffusion and the effect of fog formation on the sensible heat.…”
Section: Introductionmentioning
confidence: 99%
“…A theoretical model was developed based on Liao's modified diffusion layer theory [13] including the roughness and the suction effect. The predicted values agreed well with their experimental and literature data.…”
Section: Introductionmentioning
confidence: 99%